Know about science water - Bhanot, T.R. (Dreamland Publications New Delhi, 1999)
Know About Science - Water examines the importance of water in our lives and the environment. It discusses the water cycle, properties of water, and its role in sustaining life. Vibrant illustrations and easy-to-understand text make learning about water both informative and enjoyable for young readers.